The Analysis of Perception of Integration Processes in Armenian Society - E. S. Andreeva (Управленческое консультирование)
The article analyzes the information presented in the media and Internet resources related to the problem of the attitude of various segments of the Armenian society to Armenia’s integration policy, including the issues of Armenia’s participation in the Eurasian Economic Union, as well as the problems of Armenia’s cooperation with the EU.